2006
DOI: 10.1152/japplphysiol.00481.2006
|View full text |Cite
|
Sign up to set email alerts
|

Short-term hypoxic exposure at rest and during exercise reduces lung water in healthy humans

Abstract: Hypoxia and hypoxic exercise increase pulmonary arterial pressure, cause pulmonary capillary recruitment, and may influence the ability of the lungs to regulate fluid. To examine the influence of hypoxia, alone and combined with exercise, on lung fluid balance, we studied 25 healthy subjects after 17-h exposure to 12.5% inspired oxygen (barometric pressure = 732 mmHg) and sequentially after exercise to exhaustion on a cycle ergometer with 12.5% inspired oxygen. We also studied subjects after a rapid saline inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
62
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(70 citation statements)
references
References 65 publications
6
62
2
Order By: Relevance
“…Subjects exercised and recovered in hypoxia in an attempt to heterogeneously elevate pulmonary artery pressures and increase the probability of stress failure and/or leakage in the pulmonary capillaries. However, recent work by Snyder and colleagues demonstrated that rest and exercise in normobaric hypoxia actually caused a decrease in lung density and lung water, possibly caused by hypoxic stimulation of lymph flow from the lung (Snyder et al 2006). If lymphatic clearance rates were elevated to equal or exceed the rate of EVLW accumulation then an increase in lung density would not be measurable even during or immediately following exercise.…”
Section: Pre-exercisementioning
confidence: 99%
“…Subjects exercised and recovered in hypoxia in an attempt to heterogeneously elevate pulmonary artery pressures and increase the probability of stress failure and/or leakage in the pulmonary capillaries. However, recent work by Snyder and colleagues demonstrated that rest and exercise in normobaric hypoxia actually caused a decrease in lung density and lung water, possibly caused by hypoxic stimulation of lymph flow from the lung (Snyder et al 2006). If lymphatic clearance rates were elevated to equal or exceed the rate of EVLW accumulation then an increase in lung density would not be measurable even during or immediately following exercise.…”
Section: Pre-exercisementioning
confidence: 99%
“…pulmonary edema EVEN IN HEALTHY SUBJECTS EXTREMELY demanding endurance exercise leads to functional and structural cardiac and pulmonary changes, along with local and systemic responses, reflecting oxidative, metabolic, hormonal, and thermal stress, besides immunomodulation and inflammatory reaction (4,30,32,40,41,46). Whether interstitial pulmonary edema occurs in athletes performing heavy sea level exercise is debated (2,6,12,18,19,27,28,44,56). Interstitial pulmonary edema has been documented in endurance athletes performing heavy sea level exercise, using imaging techniques such as chest X-ray, magnetic resonance, computed tomography, and scintigraphy (17,36,56).…”
mentioning
confidence: 99%
“…letes performing heavy sea level exercise is debated (2,6,12,18,19,27,28,44,56). Interstitial pulmonary edema has been documented in endurance athletes performing heavy sea level exercise, using imaging techniques such as chest X-ray, magnetic resonance, computed tomography, and scintigraphy (17,36,56).…”
mentioning
confidence: 99%
“…Interestingly, the magnitude of the epinephrine response to altitude was six times larger in individuals with decreased FEF 25-75 versus individuals with increased FEF 25-75 . Catecholamine upregulation has been associated with stimulation of b 2 -adrenergic receptors leading to enhanced fluid clearance from the alveoli via the epithelial sodium channels and from the interstitial space via the lymph system (Berthiaume et al 1987;Sartori et al 2002;Snyder et al 2006bSnyder et al , 2007. It is possible that the greater epinephrine response to altitude in individuals with decreased FEF 25-75 may be in response to other mediators or to the accumulation of fluid in these individuals.…”
Section: Discussionmentioning
confidence: 99%
“…However, previous studies suggest that acute normobaric hypoxia may actually cause a decrease in extravascular lung water possibly due to catecholamine stimulation of b 2 -adrenergic receptors leading to an increase in alveolar fluid clearance through stimulation of epithelial sodium channels (Sartori et al 2002;Snyder et al 2006bSnyder et al , 2007. Also, it has been suggested that the lungs are more resistant to edema than other organs due to specific pulmonary vasculature properties such as a less permeable endothelium lining in the pulmonary capillaries as well as restricted movement of electrolytes and proteins (Effros and Parker 2009).…”
Section: Introductionmentioning
confidence: 99%